Indonesia Regional Representative Council Authority After Constitutional Court Decision No. 92 / PUU-X / 2012 - Bukhori Bukhori; Nizla Rohaya (Rechtsidee, 2019)
The purpose of this study was to determine the position, role and function of the DPD-RI in the Indonesian constitutional system before and after the Constitutional Court Decision No. 92 / PUU-X / 2012. The research method used is juridical normative and type of research is statutory approach, comparative approach, and conceptual approach. The results showed that a number of laws and regulations governing the DPD-RI were still less than the initial purpose of the formation of the DPD-RI. Certain articles relating to the position, function and role of the DPD-RI actually limit the authority of the DPD-RI so that it cannot function as a state institution that should have the same position as the DPR-RI. The decision of the Constitutional Court No. 92 / PUU-X / 2012 brings a new chapter in the implementation of democracy in Indonesia. The ruling of the Constitutional Court firmly provides a strategic role for the Regional Representative Council in Indonesian constitution.